Educational Tools for Prevention of Human Cystic Echinococcosis in Schoolchildren from an Endemic Area of Peru - León Córdova, Daphne (2023)
This study developed and validated educational tools for the prevention of human cystic echinococcosis (HCE) among schoolchildren from third to sixth grade in a public educational institution in the Junín Region, Peru. This quasi-experimental study consisted of three phases: 1) design of educational tools; 2) validation of the tools through expert judgment; and 3) application and validation of the tools in the field, targeting schoolchildren from third to sixth grade. The effect of the tools was evaluated by comparing knowledge before and after the intervention using a ten-question test. Four educational tools were created: a coloring storybook, a board game, a flip chart, and a museum display. Expert judgment determined strong validity for the flip chart and storybook (Aiken’s V = 1.14 and 1.21, respectively), and acceptable validity for the board game and museum display (Aiken’s V = 1.08 and 1.03, respectively). In the field evaluation, 131 students (42.8% girls and 57.2% boys), aged 8 to 13, participated. For most questions, the number of students with right answers was higher in the post-test as compared to the pre-test (p < 0.05). Similarly, there was a significant difference (p < 0.05) between the pre-test and post-test scores. The students were able to acquire knowledge through the combined use of the educational tools. It is expected that this knowledge will endure and, over time, contribute to modifying attitudes and practices to reduce the risk of HCE infection.